Windows Server 2003 security infrastructures - Clercq, Jan de, 1968- (Digital Press, an imprint of Elsevier, 2004)
Windows Server 2003 Security Infrastructures is a must for anyone that wants to know the nuts and bolts of Windows Server 2003 security and wants to leverage the operating system's security infrastructure components to build a more secure I.T. infrastructure. The primary goal of this book is to provide insights into the security features and technologies of the Windows Server 2003 operating system. It also highlights the security principles an architect should remember when designing an infrastructure that is rooted on the Windows Server 2003 OS. *Explains nuts and bolts of Windows Server 2003 security *Provides practical insights into how to deploy and administer secure Windows Server 2003 infrastructures *Draws on the experience of a lead consultant in the Microsoft security area.